How does perceived organisational support restrain social loafing of employees? The mediating role of self-efficacy and entrepreneurial bricolage - Chong Chen; Huizi Song; Daojuan Wang; Beibei Wang (Journal of Innovation & Knowledge (JIK), 2025)
The study aims to examine the determinants of social loafing by using social exchange theory and expectation theory. Specifically, we examine how self-efficacy and entrepreneurial bricolage moderate the relationship between perceived organizational support and employee social loafing. In addition, we examine the moderating effects of person-organization fit and organizational justice. Empirical evidence suggests that: 1) Being regarded as receiving assistance from an organization has a significant negative impact on social loafing. 2) Self-efficacy partially mediates the influence of perceived organizational support on social loafing. 3) As the level of person-organization fit grows, the mediating influence of self-efficacy becomes more pronounced. 4) Entrepreneurial bricolage offers a novel hypothesis to explain the hindrance of perceived organizational support on workers' engaging in social loafing. 5) An organizational justice environment effectively controls the impact of perceived organizational support on workers' entrepreneurial bricolage. The study examines the interactions between firms and employees, proposing a framework to reduce employees' social withdrawal and optimize firms' human resource efficiency.
Keywords: D22; J29; 650; Perceived organizational support; Social loafing; Self-efficacy; Entrepreneurial bricolage